Pilgrimage as Peoplehood: Indigenous Relations and Self-Determination at Places of Catholic Pilgrimage in Mi’kma’ki and the Métis Homeland - Gareau, Paul L. (Material religion, 2022)
Movement across traditional territory to sacred places has always been central to Indigenous thought, action, and governance. And these places are co-constituted by relations with the Land and Waters, with kin, and with other collective peoples, human and more-than-human. This article examines Indigenous experiences of religion and mobility with regards to places of Catholic pilgrimage in Mi’kma’ki territory and the Métis Homeland. We problematize White possessiveness and the settler colonial project by showing how ideas of religion and sedentism serve as a racializing force in governing Indigenous territories and bodies. We focus instead on Indigenous experiences and understandings of religion and mobility as relational, where (1) movement is about experiencing different relations within storied spaces and places that help familiarize and constitute traditional territory and homelands, and (2) place/places allow for nationhood and peoplehood relations to flourish. This article affirms the self-determination of Indigenous pilgrimage as engendering peoplehood relations.